Plasma-polymerized fluorocarbon Ag–Cu nanocomposites: Nanostructure optimization for superior SERS sensitivity - Joonhyuk Lee; Sung Hyun Kim; Seok-Kyun Son; Sang-Jin Lee (Applied Surface Science Advances)
Surface-enhanced Raman spectroscopy (SERS) enables the precise identification of molecules by enhancing the Raman signals of target compounds. This enhancement relies on the presence of Raman-active molecules on suitable nanostructures, where local surface plasmon resonance creates electromagnetic hotspots. This paper proposes a method to finely control the distribution of Ag and Cu nanoparticles within a plasma–polymer–fluorocarbon (PPFC) thin film by adjusting the sputtering power density to improve SERS performance. We fabricated Ag–Cu nanocomposite PPFC (CAP) thin films by sputtering at different mid-range-frequency sputtering densities, resulting in variations in the optical absorption wavelengths and changes in the Ag/Cu ratio, as confirmed by an X-ray photoelectron spectroscopy analysis. SERS measurements using rhodamine 6G demonstrated an enhancement factor (EF) of up to 108, further supported by finite-difference time-domain simulations based on nanostructures characterized by atomic force microscopy. We applied the prepared CAP thin films to contaminated surfaces and assessed their ability to enhance Raman signals for point-of-care detection. Despite a reduced EF due to the absorption of the thick polyethylene terephthalate substrate, the films generated identifiable Raman signals. This work highlights the potential of CAP thin films in creating flexible, tightly integrated, and highly sensitive SERS-active substrates.